Computational study of the effects of induced land use changes on meteorological patterns during hot weather events in an urban environment. (28th December 2012) - Vlachogiannis, Diamando; Sfetsos, Athanasios; Gounaris, Nikolaos; Papadopoulos, Athanasios
The heavy urbanisation of great cities has caused immense concern to societies due to air quality degradation and adverse changes in local climates such as abnormally high temperatures. Due to the growing demand for renewable energy resources and electrical power generation, the installation of photovoltaic (PV) panels on building roofs and other available open spaces has advanced in the recent years. Such applications are translated to land use and land cover modifications with respect to the existing situation. This work attempts to investigate the application of PVs in the city of Athens (Greece) and estimate computationally the subsequent results in maximum temperatures and wind velocities mainly during hot weather events. Those events were identified using meteorological data available from the National Centres for Environmental Prediction (NCEP) global forecasting system (GFS). Land use changes due to photovoltaic canopies have been translated into changes in surface albedo and roughness, specific heat capacities, thermal properties and evapo-transpiration in the input files of the domain of Athens (1 × 1 km 2 ) of the modelling system (Mesoscale Model 5, MM5). The model results revealed noticeable changes in the temperature and wind fields when applying the scenario of installing PV panels in the urban canopy of the city.